Functionally heterogeneous intratumoral CD4 + CD8 + double-positive T cells can give rise to single-positive T cells - Tony Li; Arielle Ilano; Marcel Arias-Badia; Diamond Luong; Hewitt Chang; Serena S. Kwek; Kathryn Allaire; Arun Chumber; Mason Sakamoto; Matthew Clark; Averey Lea; Mark Bridge; et al. (Proceedings of the National Academy of Sciences, 2026)
Conventional single-positive (SP) CD4 + and CD8 + T cells recognize tumor antigens and help mediate clinical responses with cancer immunotherapy. Double-positive CD4 + CD8 + (DP) T cells have also been described in human cancers, but their role in the tumor microenvironment remains unclear. By generating a multiomic single cell atlas of DP and SP T cells, we find that DP T cells possess phenotypic heterogeneity similar to SP T cells that includes multiple clonally expanded populations of cytotoxic DP T cells in human renal cell carcinoma (RCC). These intratumoral DP T cells can mediate both MHC class I- and class II-dependent killing of autologous tumor cells. In addition, transcriptional profiling of DP TCR-bearing T cells revealed a gene signature enriched for clinical responders to PD-1 blockade in advanced RCC. We confirm prior observations of SP T cells transitioning into DP T cells and more notably, demonstrate that intratumoral T cells are capable of bidirectional differentiation in which DP T cells serve as precursors to SP T cell sin vivo. In the latter scenario, intratumoral DP T cells are shown to express Rag2 , suggesting that the tumor may act as an extrathymic site of T cell development. These findings reveal the multiple roles that DP T cells can possess in antitumor immunity.